KEBERMAKNAAN HIDUP MAHASISWA SEKOLAH TINGGI THEOLOGIA NAZARENE INDONESIA DITINJAU DARI TINGKAT RELIGIUSITASNYA - Berima Ritonga dan Esti Listiari (Jurnal Psikologi, 2006)
The objective of this research is examining the positive relationship between the religiosity level and the meaningful of life variables. There are four aspects of the meaningful of life variable such as the life direction, understanding of self potentiality, ability to beliave positively in facing reality, and ability to engage his or her social interaction positively. The research hypothesis is significant with r . = .446 and p<.OL The determinant coefficient is nearly 20%, and this obviously needs other additional independent variables such as personality. It will also interesting when widening the research subjects into other religions such as Moslems, Buddhist, or Hindu.